Keadilan Bagi Masyarakat Korban Kriminalisasi (Suatu Tinjauan Sosiologis Filosofis Tentang Keberlakuan Hukum Yang Jauh Dari Keadilan) - Sastiono Kesek (Prodi Ilmu Administrasi Negara, 2016)
Applicability of Law in Indonesia is still far from the goal of the law itself, namely Justice, Public Order and Peace. It is very noticeable is in connection with arrangements for the protection of members of the public from arbitrary actions of law enforcement officers. That in Indonesia is already a lot of people who suffered persecution from law enforcement (police) where many cases community members to be prosecuted and detained for allegedly committing a crime then the Court is not proven, but the community was already on hold months that have resulted in family life to be disrupted. Legislation in Indonesia has not provided a holistic and comprehensive protection of the victims of the criminalization of the police so that the issue of justice for victims of criminalization becomes important because if one person is having problems, the law then the problem can affect the social life of the family and even the community at large.